Professionalism of Employees Regional Market Company of Tomohon City - Simbala, Cinthya (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Regional Market Company of Tomohon City is an institute that has a rule and aresponsibility in field of public service especially for marketer who works in the market of Tomohon.Regional Market Company of Tomohon city have their own job to revitalization traditional market inTomohon city so that they can be able to compete with modern market, with expectation will be give areal benefit for acceleration of the economics growth of the people through the Economicempowerment, making the market of Tomohon city to be professional, benefit, and independent.Implementation of job already felt by the people in Tomohon city with the various of achievement thatobtained by Tomohon market. Professionalism of employees is most easily to rate and to perceive bypeople through the quality of public services which is conducted by the employees themselves. Poorpublic services reflects to employees who are not professional and has a low performance.The aim of this study is to observe the professionalism of employees in Regional MarketCompany of Tomohon city in providing the public services for marketer.The methodology used was qualitative research. Primary data were collected through in-depthinterviews of 15 informants including President Director, General Manager, head of division, staffs,and marketers. Secondary data were obtained Through a certain form of supporting information inthis research, related documents with professionalism of employees such as decree, main task andfunctions, chart, services procedures, work report and the others document regarding to publicservices. Then, data obtained were analyzed with the categorization and the reduction data.The result of this study shows that professionalism of employees in Regional Market Companyof Tomohon City for implementation public service still needs more improvement. Employees inRegional Market Company have not produced creativity, Innovation and attention to responsibility indaily works. In addition the employees are not flexible or just waiting for command and moves,without creativity.It is suggested that technical guidance needs to improve in order to support the maximumservices for marketers. Finally, the innovation of employees is expected more adapt with thedevelopment of modern technology and the responsibility of employees in order to give a better publicservice. Also this is important to accommodate the aspiration of marketers which in turn answersevery complaint of marketer.Key words : Professionalism,Creativity,Innovation,Responsivity